Strategi Pengelolaan Reklamasi Berkelanjutan dengan Pendekatan MICMAC di Kecamatan Pinang Raya Kabupaten Bengkulu Utara - Rokky Gumanti; Faiz Barchia; Reflis Reflis; Gunggung Senoaji; Urip Santoso (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2025)
This study aims to formulate a sustainable reclamation management strategy using the MICMAC (Matrix of Crossed Impact Multiplications Applied to a Classification) approach in Pinang Raya District, North Bengkulu Regency. Mining activities in this region have caused ecological degradation, making post-mining land reclamation crucial. The research employs a qualitative method with data collection through field observations, questionnaires, and interviews involving stakeholders from mining companies, plantation companies, and local communities. The MICMAC analysis identified key driving factors in sustainable reclamation, such as regulatory enforcement, personnel management, public understanding, and community participation. The study results show that sustainable reclamation requires integrated planning involving strengthened legal frameworks, capacity building, and participatory approaches. Strategies should prioritize technical implementation (land arrangement, topsoil distribution, and local vegetation planting) and social inclusion to ensure ecological restoration while enhancing community welfare. This approach contributes to achieving the Sustainable Development Goals (SDGs) and offers a reference for sustainable post-mining land management in Indonesia.